PEMBOROSAN KATA RAGAM BERITA MENURUT KAJIAN BAHASA - Jupriono, D. (TANDA, 2022)
This article explores the language use in newspaper columns. The principle of frugality, beauty, coherence, and language feature as language varieties should be considered in language use in newspaper columns. Thus, various news can be studied from various approaches. News varietes redundancy is treated differently by the stylistics, semantics, discourse analysis and sociolinguistics because of different language design orietantion of each field. Stylistics and semantics approach language use in expalanative descriptive point of views that results in regarding redundancy in news varietes as normal and acceptable. In contrast, discourse analysis and stylistics approach the language use in normative prescriptive point views that results in regarding redundancy in news varietes as mistakes should be avoided.